1997
DOI: 10.1097/00005768-199707000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Compartmental shifts of calcium and magnesium as a result of swimming and swimming training in rats

Abstract: To describe accurately the mineral changes (Ca and Mg) provoked by swimming, the aims of this study were to analyze those tissues that, with regard to their mineral content, can better classify individuals performing both swimming until exhaustion and swimming as training and to know the shifts of these minerals between different tissues after a single session of swimming until exhaustion and after training. Wistar rats were distributed into 12 groups, six male and six female (N = 10): 1) control rest group (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…A muscle biopsy together with an overloading protocol could be a more realistic approach to analyze Mg redistribution between body compartments, but these invasive protocols cannot be performed during such a demanding race as “Vuelta a España”. Therefore, serum Mg determination is not sufficient to paint a full picture of redistribution of Mg from one storage area (release) to an active site (muscle or adipose tissue), as previously documented [1,11,23,26,27,28]. Also, we have to consider the losses through sweat and urine, which are estimated at 10–20% [3].…”
Section: Discussionmentioning
confidence: 99%
“…A muscle biopsy together with an overloading protocol could be a more realistic approach to analyze Mg redistribution between body compartments, but these invasive protocols cannot be performed during such a demanding race as “Vuelta a España”. Therefore, serum Mg determination is not sufficient to paint a full picture of redistribution of Mg from one storage area (release) to an active site (muscle or adipose tissue), as previously documented [1,11,23,26,27,28]. Also, we have to consider the losses through sweat and urine, which are estimated at 10–20% [3].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, we have recently observed that Ca and Mg undergo compartmental redistribution in rats after acute and maintained exercise. These changes allow to classify individuals on the basis of their tissue mineral content [33].…”
Section: Discussionmentioning
confidence: 99%
“…The swimming exercise performance test was used as previously described with some modifications [11]. A rat was taken out from each treatment group for swimming exercise and loaded to a constant weight corresponding to 5% of the individual body weight.…”
Section: Methodsmentioning
confidence: 99%